Da inação legislativa à criminalização: um olhar sociológico sobre a equiparação da LGBTIfobia a racismo pelo Supremo Tribunal Federal - Ribeiro, Paulo Thiago Carvalho Soares (2021)
In June of 2019, with 8 positive votes out of 11, the Supreme Federal Court (SFC) agreed that the Direct Action of Unconstitutionality by Omission (DAUO) n.º 26/DF is partially precedent, judged alongside the Injunction Warrant (IW) n.º 4.733/2019 to recognize that the National Congress was in delay when it decided to not criminalize sexual orientation and gender identity prejudice conducts. The ministers agreed that there was negative commandment in the Constitution in the way to criminalize said conducts. And, after more than thirty years, there was no law for that. The SFC then, judged that as long as the Congress don’t legislate about it, the discrimination resulted on LGBTphobic actions is now a racism crime, aware of the social-historical character of the race category in which the LGBTI people would fall on. This equivalence and the criminalization via the judiciary have no precedents in the world. So, the following paper had the intention of contribute to the understanding of the social and political dynamics which resulted in the SFC criminalizing LGBTphobic conducts as racist acts. In order to do this research, there was a bibliographical exploration to understand what is racism and racialization, and what is the meaning and fundaments of the “social races” concept, understanding also the theories about gender and sexuality and the influence of constitutional segmentation on the democracy. Also, processual documents of the verdict, like Minister votes and the initial petition were analyzed. From what was researched, it was noted a constancy in the tendency of judicialization LGBTI people in Brazil. And the country is even becoming a highlight among others because of the fact that the assurance of rights always comes from judicial decisions. About social race, it’s agreed that every race is social. So, there was no innovation when it comes to the concept or scientific understanding. What happened was a provisional strategic racialization to protect the LGBTI people under the main anti-discriminatory law of the country, the Law n.º 7.716/89, which punish the resulting crimes of discrimination or prejudice by race, ethnicity, color of the skin, religion or national procendency.